Thyroarytenoid muscle fiber orientation regulates the ability to modulate vocal fold vertical thickness - Tsukasa Yoshinaga; Zhaoyan Zhang (PLoS ONE, 2025)
While all speakers modulate their voice quality, some speakers do so more easily than others. Previous studies suggest that the ability to modulate voice quality depends on the ability to control vocal fold medial surface vertical thickness, among other factors. While it is well known that vocal fold vertical thickness can be increased by an inferior medial bulging of the vocal folds due to actions of the thyroarytenoid (TA) muscle, the underlying mechanism of how TA muscle activation produces inferior medial bulging remains unclear. In this computational study, we show that the TA muscle fiber orientation had a large effect on the extent of inferior medial bulging and vertical thickness increase under TA muscle contraction in a three-dimensional model of laryngeal muscle activation based on high-resolution magnetic resonance imaging. Maximum inferior medial bulging and thickness increase occurred when the TA muscle fiber orientation angle ranged between 22–32° relative to the anterior-posterior direction. At these optimal fiber angles, TA muscle activation was able to induce a horizontal rotation of the arytenoid cartilage, which medialized the vocal process and the inferior portion of the medial surface more than the superior portion of the medial surface, thus increasing vertical thickness. In contrast, the lateral cricoarytenoid muscle induced a rocking rotation of the arytenoid cartilage, which medialized the superior medial surface slightly more than the inferior medial surface, and thus had an opposite and much-reduced effect on vocal fold thickness. It is hypothesized that potential individual differences in TA muscle fiber orientation may contribute to individual differences in the ability to modulate voice quality.